Transient expression of hemagglutinin antigen from canine influenza virus H3N2 in Nicotiana benthamiana and Lactuca sativa - Maharjan, Puna Maya; Choe, Sunghwa (Clinical and experimental vaccine research (Seoul), 2019)
Canine influenza virus (CIV), H3N2, carries potentiality for zoonotic transmission and genetic assortment which raises a concern on possible epidemics, and human threats in future. To manage possible threats, the development of rapid and effective methods of CIV vaccine production is required. The plant provides economical, safe, and robust production platform. We investigated whether hemagglutinin (HA) antigen from Korea-originated CIV could be produced in and lettuce, by a DNA viral vector system. We used DNA sequences of the HA gene from Korean CIV strain influenza A/canine/Korea/S3001/2015 (H3N2) for cloning into a geminiviral expression vectors to express recombinant HA (rHA) antigen in the plant. -mediated infiltration was performed to introduce HA-carrying vector into host plants cells. Laboratory-grown , and grocery-purchased or hydroponically-grown lettuce plant leaves were used as host plants. CIV rHA antigen was successfully expressed in host plant species both and by geminiviral vector. Both complex-glycosylated and basal-glycosylated form of rHA were produced in lettuce, depending on presence of endoplasmic reticulum (ER) retention signal. In terms of rHA expression level, canine HA (H3N2) showed preference to the native signal peptide than ER retention signal peptide in the tested geminiviral vector system. Grocery-purchased lettuce leaves could serve as an instant host system for the transient expression of influenza antigen at the time of emergency. The geminiviral vector was able to induce expression of complex-glycosylated and basal-glycosylated rHA in lettuce and tobacco.